IMPLEMENTATION OF ISLAMIC POLITICAL ETHICS IN INDONESIA: STUDY OF IBN KHALDUN'S THOUGHTS - M. Yusran S; Azizah, Nurul; M. Hairul; Kurniati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research is entitled